Using net games to stimulate the motor competence of elementary school students - Uray Gustian; Putra Sastaman; Zsolt Nemeth (Jurnal Keolahragaan, 2023)
Motor competence is essential to develop an active lifestyle, a healthy weight status, and a physical-activity habit. Motor competence stimulation focus on measuring the physical activity of playing games. The study investigated the potential improvement of motor skill by playing net games. Through the study, students are taught to make important decisions and acquire tactical knowledge by simplifying complex games. This research adopted an experimental design using One Group pretest-posttest method. Samples were collected through random sampling method in two classes of a selected elementary school. The Games Performance Assessment Instrument (GPAI) and the Gross Motor Development Test version 2 (TGMD-2) were used to assess students' playing understanding, motor skills, and numeric knowledge. Utilizing quantitative descriptive analysis, data were examined. The findings showed that the posttest values for motor skill aspects (95) were greater than the pretest results (88, 5). The average increase of each component for playing game was execution skill of 0.05, decision-making of 0.04, opponent coverage of 0.03, and overall of 0.05. Different test results show that t-test (t=4.50), both for game understanding and motor skill aspects, which were greater than t-tables (1,796). The statistics showed that the skills after treatment were significantly different from the students’ ability before treatment. This improvement in decision-making, technical execution, cover, support, game performance, game participation, pleasure, perceived competence, and intention to engage in physical activity is attributable to the usage of net games. The conclusion is that the use of net games is effective in improving the motor competence of elementary school students. However, the study only involves a small number of students, hence it is recommended for including a larger number of students in the further research, as well as using more rigid study design (control group) and take in different elementary schools.